2012
DOI: 10.1523/jneurosci.6112-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning Selectively Refines Orientation Representations in Early Visual Cortex

Abstract: Although practice has long been known to improve perceptual performance, the neural basis of this improvement in humans remains unclear. Using fMRI in conjunction with a novel signal detection-based analysis, we show that extensive practice selectively enhances the neural representation of trained orientations in the human visual cortex. Twelve observers practiced discriminating small changes in the orientation of a laterally presented grating over 20 or more daily one-hour training sessions. Training on avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 39 publications
14
121
0
1
Order By: Relevance
“…This classifier performed well in regions V1-V3 (t (11) ϭ 9.87; p ϭ 8.4 ϫ 10e-7; Fig. 2A, yellow bars), consistent with previous work (Kamitani and Tong, 2005;Jehee et al, 2011Jehee et al, , 2012. To investigate whether the orientation-selective responses for recalled gratings were similar to stimulus-driven activity, a third classifier was trained on activity patterns generated by passive viewing (P) and tested on the recalled orientation from neural patterns during cued recall (R).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This classifier performed well in regions V1-V3 (t (11) ϭ 9.87; p ϭ 8.4 ϫ 10e-7; Fig. 2A, yellow bars), consistent with previous work (Kamitani and Tong, 2005;Jehee et al, 2011Jehee et al, , 2012. To investigate whether the orientation-selective responses for recalled gratings were similar to stimulus-driven activity, a third classifier was trained on activity patterns generated by passive viewing (P) and tested on the recalled orientation from neural patterns during cued recall (R).…”
Section: Resultssupporting
confidence: 91%
“…Our findings dovetail with previous neuroimaging work that showed that voxel patterns in visual cortex are not only predictive of bottom-up visual processes, such as specific visual stimulus properties (Kamitani and Tong, 2005) and unconscious perception of a stimulus (Haynes and Rees, 2005), but that visual cortex is also involved in complex, top-down visual computations (Mumford, 1991;Lamme and Roelfsema, 2000): several fMRI studies showed that the participants' attentional state (Kamitani and Tong, 2005;Liu et al, 2007;Serences and Boynton, 2007;Jehee et al, 2011) and stimulus expectation can be predicted from activity patterns in early visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that if training could improve the neural representations of the motion stimuli (especially in the trained direction), as suggested by the TMS and psychophysical results, it was possible that decoding accuracies for the orthogonal directions could be improved by training. Similar approaches have been used previously (19)(20)(21). Before training, a repeated-measures ANOVA revealed a significant main effect of stimulus coherence level and a significant interaction between stimulus coherence level and area [V3A and MT+; both F(1,11) > 7.87l P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 53%
“…First, the performance gains associated with visual perceptual learning involve plasticity-modulated physiological changes in V1 (Schoups et al 2001;Watanabe et al 2002;Fahle 2004;Pourtois et al 2008;Bao et al 2010;Vogels 2010;Sale et al 2011;Jehee et al 2012) and are increased by cholinergic enhancement (Rokem and Silver 2013). Second, temporal association and sequential motion enhances familiar object recognition and representation (Stone 1998(Stone , 1999Wallis 2002;Newell et al 2004;Vuong and Tarr 2004;Cox et al 2005;Sinha 2008, 2009;Li and DiCarlo 2008), showing that the primate visual system learns to use both spatial and temporal information.…”
mentioning
confidence: 99%